Phytochemical And Biological Investigation On Three Species Of The Genus Homalomena - ., Abdul Hamid (2011)
Three species from the genus Homalomena, namely, H. pineodora, H. sagittifolia and H. coerulescens were chosen for this particular research since they have long been used in traditional medicine. The essential oils of the leaves and rhizomes of the three species were isolated by hydrodistillation and analyzed by capillary GC and GC-MS, utilizing two columns of different polarities. Isolation and purification of non-volatile phytochemicals were carried out using various solvent systems and chromatographic methods and their structures were determined by using spectroscopic methods such as FT-IR, one and two dimensional NMR experiments: 1H-NMR, 13C-NMR, DEPT 45, DEPT 90, DEPT 135, 1H-1H-COSY, 1H-1H-NOESY, 1H-13C-HMQC, 1H-13C-HMBC, GC-MS, DP-MS and LR-MS. The essential oils, crude extracts and some of the isolated compounds were assayed for biological activity (antibacterial, acetylcholinesterase enzyme inhibitory activity and anti-inflammatory activity) to evaluate their reported traditional uses.